Pembelajaran Menulis Puisi dengan Metode Teaching at the Right Level (TaRL) Berbantuan Canva di Kelas VI SD Negeri 3 Krakitan Tahun Pembelajaran 2025/2026 - Beta Herlina Liderita; Sukini Sukini; Agus Yuliantoro (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to describe the implementation of poetry writing learning using the Teaching at the Right Level (TaRL) method assisted by Canva media in sixth grade at SD Negeri 3 Krakitan in the 2025/2026 academic year. The research employed a qualitative approach with a case study design. The research subjects consisted of sixth-grade students and an Indonesian language teacher. Data were collected through observation, interviews, poetry writing tests, and documentation. Data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results show that the implementation of the Teaching at the Right Level (TaRL) method enables teachers to adjust learning activities according to students’ ability levels, making the learning process more adaptive and inclusive. The use of Canva also increases students’ motivation, creativity, and engagement in writing poetry. In addition, students’ poetry quality improved in terms of diction, structure, and visual creativity. The integration of the Teaching at the Right Level method with Canva creates a more interactive and engaging learning environment while supporting students’ digital literacy development.